Adequação dos Regulamentos nas Áreas de Térmica, Acústica, Segurança Contra Incêndios e Ventilação à Reabilitação de Edifícios de Habitação
The preservation of the existing Portuguese built heritage and the whole rehabilitation sector as a whole has been neglected for many years. Recently, however, the levels of awareness towards this problem have risen and more importance has been placed in protecting the existing assets, not only for cultural reasons but also as a strategy for urban and economical sustainability. This document's main objective is to study the adequacy of existing legislation in some of the many areas of specializations related to construction. The analyzed documents will be the current regulations for thermal behaviour, acoustic requirements and fire safety as well as the Portuguese standards for natural ventilation of dwellings. On the foundation of this analysis there is a sample of buildings specially chosen to represent various eras and construction types. The sample includes a traditional one family house from the countryside, an urban building from the late nineteenth century, a building where activities other than housing take place from the 60s, some residential towers from the 70s and a complex of social housing dating from the 80s. Each of these buildings has been submitted to his own rehabilitation process which, depending on the situation has been more or less intrusive. On the newer buildings, the interventions were generally quite superficial and limited to dealing only with recovering the elements of their exterior envelope without introducing any particular changes. On the two older buildings though, despite maintaining their overall appearance, the interventions were significantly deeper changing some of the buildings' features. By taking these processes into consideration this document will focus on determining whether the buildings meet the requirements from the studied technical documents detecting the major inconsistencies or difficulties related to rehabilitation in general in hopes that, future versions of the studied regulations and standards will correct some of these flaws and thus protect the built Portuguese heritage. KEYWORDS: rehabilitation, thermal behaviour, acoustics, fire safety, ventilation.